The perceived impact of infertility on romantic relationships and singlehood among adult survivors of childhood cancer. Issue 3 (1st February 2019) - Lehmann, Vicky; Ferrante, Amanda C.; Winning, Adrien M.; Gerhardt, Cynthia A.
Abstract: Objective: To examine whether adult survivors of childhood cancer perceive a direct impact of potential/confirmed infertility on their romantic relationships/singlehood. Methods: Open‐ended qualitative phone interviews were conducted with 57 adult survivors of childhood cancer and analyzed through thematic content analysis until saturation was reached ( N = 30). Results: Interviews revealed three major themes: (1) impact on survivors, (2) impact on partners/romantic relationships, and (3) alternative routes to parenthood. An overarching theme related to (4) timing also emerged. In describing the impact on themselves, survivors shared subthemes of (1.1) becoming aware of infertility as potential late effect of childhood cancer treatment and (1.2) their emotional reactions (ie, worries/concerns, distress, guilt, no emotional reaction). The impact on partners/romantic relationships also included subthemes: (2.1) partner communication, (2.2) partner reactions, and (2.3) the journey of active family planning. Conclusions: The perceived impact of potential/confirmed infertility on romantic relationships of adult survivors of childhood cancer varied across individuals and time. Its presence or absence depends on life circumstances (eg, marital status, life goals), and if present, negative effects were typically resolved over time by having a pregnancy. Other survivors found joy and comfort in step‐children, considering adoption, or embracing a life without children. While more research is needed, findings indicate that discussions about infertility and fertility testing should be tailored to individual survivors and their needs, which may change over time. Timely referrals to reproductive specialists or adoption agencies are recommended for those who want children and have difficulties conceiving.